TRANSFORMING ‘URF-BASED CULTURAL VALUES INTO ISLAMIC EDUCATIONAL VALUES: LESSONS FROM THE KULFOT TRADITION OF THE SERAM COMMUNITY, MALUKU, INDONESIA - Muhammad Asykur Muchtar (IAIN Bone, 2026)
Contemporary Islamic education faces increasing challenges in maintaining its relevance amid rapidly changing social and cultural contexts. This situation highlights the need for educational approaches that are responsive to local wisdom and community realities. This study aims to examine the educational values embedded in the Kulfot tradition of the Seram community in Maluku and to explore how these values can be transformed into Islamic educational values through the framework of ‘urf. Employing a qualitative library research approach, the study draws on literature related to ‘urf, Islamic law, local wisdom, indigenous knowledge, and Islamic education, as well as studies on cultural traditions in Maluku. Data were collected through document analysis and examined using content analysis and thematic analysis. The findings reveal that Kulfot embodies core values such as solidarity, cooperation, collective responsibility, social harmony, and deliberation. These values meet the criteria of al-‘urf al-ṣaḥīḥ and function as mechanisms for cultural learning and intergenerational value transmission. The study further shows that ‘urf serves not only as a means of legal validation but also as an epistemological bridge that connects local cultural practices with Islamic educational values. Based on these findings, the study proposes a conceptual model of Culture–‘Urf–Education, which illustrates how local wisdom can be transformed into educational values within an Islamic framework. The findings contribute to the development of culturally responsive Islamic education, character education, and community-based learning, while enriching discussions on the relationship between culture, Islamic law, and education in Muslim societies.